2404. Telavancin (TLV) and Vancomycin (VAN) Activity and Impact on Mechanical Properties When Incorporated into Orthopedic Bone Cement. (26th November 2018) - Bishop, Aaron; Kim, Sunjung; Squire, Matthew; Ploeg, Heidi-Lynn; Rose, Warren
Abstract: Background: To increase available antibiotics for local administration in total joint replacements, this study investigated TLV and VAN added to Palacos® bone cement. Mechanical properties and antimicrobial activity of eluted antibiotics on common causative orthopedic implant pathogens were assessed. Methods: Palacos (40 g package) samples were loaded with TLV or VAN powder (control 2.0 g) to test drug activity and mechanical properties: bending, compression, and fracture toughness. Samples were prepared following clinical standards and as previously described (Slane et al., 2014 MSE 42: 168–176). All mechanical samples were wet cured for 21 days in PBS at 21 o C before testing in accordance with ISO 5833. With a starting inoculum of 10 3 CFU/mL, antibiotic activity was measured for 14 days against: two methicillin-resistant S. aureus, one methicillin-susceptible S. aureus and one S. epidermidis . Results: The eluted dosages from samples with 0.25 g VAN or more per Palacos package were sufficient to eliminate a 10 3 CFU/mL inoculum of S. aureus organisms. 2.0 g of TLV was required to achieve the same bactericidal effect. TLV 2.0 g was able to fully clear the initial inoculum of a high biofilm producing S. epidermidis . No tested vancomycin dosage replicated these results. Adding more than 0.5 g of TLV or VAN per Palacos package reduced compressive yield strength to (VAN) or below (TLV) the ISO 70MPa minimum. Fracture toughness and flexural strength were not significantly altered with either antibiotic. Conclusion: Adding either TLV or VAN to Palacos before polymerization reduced bending properties similarly but maintained ISO standards. More VAN than TLV can be added and still maintain compressive yield strength above ISO requirements (1.0 g VAN vs. 0.5 g TLV). VAN eliminated the tested S. aureus strains at a lower added mass. However, TLV was more effective against a high biofilm producing S. epidermidis . VAN was highly effective at eliminating a bacterial inoculum consistent with surgical contamination while maintaining ISO standards. The authors would like to acknowledge Theravance Biopharma US, Inc. for their support and funding. Disclosures: A. Bishop, Theravance: Investigator, Educational support, Research support and Salary. S. Kim, Theravance: Investigator, Research grant and Research support. W. Rose, Theravance: Consultant and Grant Investigator, Consulting fee and Research grant.